Prevalência e distribuição de lesões podais em vacas leiteiras criadas em free stall - Ebling, Rafael Costa (2018)
The prevalence of lameness is a growing concern in dairy cattle and is usually related to the type of animal rearing and to risk factors, especially those of environmental, nutritional and genetic origin. As a consequence, there is the occurrence of foot lesions, caused by poor weight distribution in lame cows, causing pain, which decreases welfare and results in large losses of productivity in the herd. The objective of this study is to estimate the prevalence of lameness and the occurrence and distribution of foot lesions in dairy herds kept in a free stall system, as well as to evaluate their correlation with the main risk factors. The factors were evaluated in a questionnaire through questions such as whether preventive casing is carried out on the property, use of foot bath, dimensions and type of bed used, type of floor and cleaning frequency, length of stay in the waiting room, as well as which is the main health problem and which is the greatest cause of involuntary discard. The study included 10 farms distributed in 7 cities of Rio Grande do Sul. The Cows were examined for their body condition score (BCS) and locomotion score (LS). The foot examination, lesion classification and the hoof trimming of the animals were performed. Of the 491 animals, 37.2% presented lameness and 465 foot lesions, 81.4% of which were observed in the hind limbs and 18.6% in the thoracic limbs. Of the lesions in the limbs, 47.1% were of infectious origin and 52.9% were noninfectious. The main lesions were sole ulcer (31.6%), digital dermatitis (30.3%), thin soles (12%) and interdigital dermatitis (11.2%). Cows aged 4 to 6 years had a higher concentration of lesions and degree of LS. Only the question regarding the use of foot bath was not associated with the foot injuries, since the other questions confirm that the occurrence of injury is associated with the predisposing factors questioned. The properties that perform preventive hoof trimming reduced in 55% the chances of lameness in their herd. The results show that dairy cows raised in a free stall system have a high prevalence of lameness and of foot lesions. These data should be taken into account when altering the livestock management of these animals, in order to reduce the significant economic losses in the herd.